Gender and ATR vowel space in Dholuo - Ochieng, Merceline; Itumo, Joshua; Kiguru, Gatitu (AAeO - Afrikanistik-Aegyptologie-Online, 2026)
This paper investigates the acoustic realization of Advanced Tongue Root (ATR) vowel contrasts in Dholuo, with particular attention to gender-conditioned variation in vowel production. Using Lobanov-normalized formant measurements (F1 and F2), the study analyzes speech data from eight native speakers (four female and four male) representing two dialect regions, Kisumu South Nyanza (KSN) and Boro-Ukwala (BU). The analysis focuses on the distribution of the nine Dholuo vowels in acoustic space and the realization of four ATR vowel pairs (/i–ɪ, e–ɛ, o–ɔ, u–ʊ/), with /a/ treated as neutral. To assess the reliability of observed acoustic differences, analyses of variance (ANOVA) were conducted on normalized F1 values across vowel categories and speaker groups. The results show that ATR contrasts are consistently reflected in the acoustic data, with [+ATR] vowels exhibiting lower F1 values than their [−ATR] counterparts. The statistical analysis confirms that these differences are significant across the vowel inventory and that both vowel category and gender contribute to variation in F1, with a significant interaction between the two factors. This pattern is particularly robust in the female data, where clear separation is observed across all vowel pairs. In the male data, ATR distinctions are generally maintained but show reduced consistency, especially in the high front pair /i–ɪ/, where the expected pattern is weakened. Vowel space analysis further indicates that female speakers produce more clearly differentiated vowel categories, while male speakers exhibit greater dispersion and overlap in certain regions of the acoustic space. Overall, the findings provide phonetic evidence for the acoustic implementation of ATR contrasts in Dholuo, demonstrating that while the contrast is systematically maintained, its acoustic reali-zation varies across vowel pairs and speaker groups.